Pengaruh Brand Performance Terhadap Keputusan Nasabah Dengan Competitive Advantage dan Digital Marketing Sebagai Variabel Intervening pada PT. Alami Fintek Sharia - Jaya Purnama (Universitas YARSI, 2023)
PT. Alami Fintek Sharia has been successful in dominating the market for sharia-based fintech. This study examines how clients or consumers of PT. Alami Fintek Sharia select the products it provides, considering the enormous growth witnessed by that company. In PT. Experience Fintech Sharia, this study investigates how brand performance impacts customer choice, which is mediated by digital marketing and competitive advantage. Facts were collected from 170 respondents using a Likert scale questionnaire. This study found that brand performance influences competitive promotion. Likewise with brand performance on digital marketing, brand performance on consumer decisions, competitive advantage on consumer decisions, and consumer decisions influenced by digital marketing. However, it was also found that indirectly, there is no relationship between brand performance on consumer choice through competitive advantage, but brand performance on consumer choice is significantly influenced by digital marketing.